Implementation of Cooperative Learning Model with Make A Match Type on Students Learning Outcomes in Elementary School - Rahma, Annisa; Haviz, M (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This study aims to determine the effect of the Make A Match learning method on student learning outcomes in elementary schools. This type of research is Quantitative research with True Experimental Design. The design used in this research is the pretest-posttest control group design. Sampling was done by random sampling technique. The data collected used observation, tests and documentation, while the research data were analyzed using descriptive statistics and inferential statistics. The results showed that this learning model had an effect on the learning outcomes of elementary school students. The application of the Cooperative Learning Model Make A Match is higher than the pretest average. Thus, the make a match model is an important part of improving student learning outcomes and is a choice of various methods for teachers